What Can Cellular Redox, Iron, and Reactive Oxygen Species Suggest About the Mechanisms and Potential Therapy of COVID-19? - Muhoberac, Barry B. (Frontiers in Cellular and Infection Microbiology, 2020)
Accumulating evidence suggests that there are important contributions to Covid-19 from redox imbalance and improperly coordinated iron, which cause cellular oxidative damage and stress. Cellular reductants are important as reactive oxygen species (ROS) scavengers and to power enzymatic repair mechanisms, but they also may help generate toxic ROS. These complicated interrelationships are discussed in terms of a cellular redox/iron/ROS triad, including reductant and chelator concentration-dependent effects and altered cellular signaling, as well as specific implications for therapeutic interventions.